(3GdCSS GdfaSjI ddfeh ef GdWahdI Edi GdTjNhNI (B/s - (3GdSjO, aDGO GdHgjs ((3GdbGgQI (B:s (3OGQ GdacQ GdYQHj,s, 1998)
(3OQGSI JegjOjI ddfeh GdfaSj(B.s
(3jTJed Ydi cTGaGJ(B.s
(3HHdjhLQGajI (B: (3U(B. 394.s
Keywords: (3Yde GdfaS GdGQJbGFjs; (3GdCWaGds -- (3fehs